Ecocriticism and Environmental Themes in 21st Century Fiction - Usman, Muh. Ilham; Anis, Nina (Journal of Humanities Research Sustainability, 2025)
Background. This research examines how environmental themes are presented in 21st-century literature and the extent to which these themes influence readers’ ecological awareness. In recent years, literature has increasingly served as a platform to address environmental issues, reflecting growing global concerns about climate change, biodiversity loss, pollution, and ecological degradation. Fictional narratives have the power to shape public perceptions by portraying the intricate relationship between humans and nature, raising awareness about the consequences of human actions, and encouraging sustainable behaviors. This study seeks to understand how contemporary authors incorporate environmental themes into their works and how readers respond to such narratives. Purpose. The main objective of this research is to explore how environmental narratives in contemporary fiction affect readers’ perceptions, awareness, and attitudes toward environmental issues. It aims to identify the most common environmental themes used in 21st-century literature and assess their potential to promote ecological awareness and encourage conservation efforts. Method. The research employs a qualitative approach, combining textual analysis and in-depth interviews with readers. Thirty contemporary literary works were purposively selected for analysis, covering various genres and cultural backgrounds. The environmental themes, narrative techniques, and ecological messages embedded in these works were examined, while interviews provided insights into how readers interpreted and responded to these narratives. Results. The study finds that environmental themes such as climate change, deforestation, pollution, species extinction, and ecological rehabilitation are prominently featured. These themes effectively engage readers, fostering greater awareness and critical reflection on environmental issues. Conclusion. The study concludes that 21st-century literature plays a significant role in shaping ecological awareness and inspiring readers to take an active role in environmental conservation efforts. Through engaging storytelling, literature can serve as a powerful tool to influence ecological consciousness and promote sustainability.